Perspectives On Wisdom And Engagement In Learning Among Undergraduate Students - Bete, Haider Kowel (Universiti Malaysia Sarawak (UNIMAS), 2014)
The purpose of this study was to investigate the perspective on wisdom and engagement in learning among undergraduate students. The research instrument used for this study was an open-ended questionnaire. This research was carried out in University Malaysia Sarawak (UNIMAS). The targeted group of participants for this research was the undergraduate students from UNIMAS. The population for the study focused on the undergraduate students who were selected to participate in this study through the convenience sampling method. The study revealed that undergraduate students’ various definition of wisdom-characteristics mirror those found in the existing body of literature, though it was unclear from the responses collected whether the participants believe that wisdom is single trait or multi-dimensional construct as scholars have suggested. Still, undergraduate students generally indicated that developing wisdom was both attainable and important for reasons that impacted both themselves and others. Furthermore, undergraduate students believed that they already possessed traits related to wisdom. Besides, undergraduate students believed that formal education played a partial role in helping them to develop wisdom. Finally, undergraduate students believe that wisdom played a partial role in helping them engage in their learning. Through this and further studies, humanity could move closer to understanding and pursuing what Erikson (1968) referred to as the highest human achievement: wisdom.